Prebiotic potential of gum Arabic for gut health - A. M Elnour, Dr. Ahmed; Hamid Nour , Abdurahman; Musa, Khalid Hamid; Rasheed, Zafar (International Journal of Health Sciences, 2023)
Gum Arabic (GA), traditionally used as a food stabilizer, demonstrates potential as a health-promoting prebiotic, beneficially modulating the human gut microbiome. A balanced microbiome is crucial for maintaining overall health and preventing diseases such as inflammatory bowel disease and obesity. GA’s non-digestible nature allows it to ferment into short-chain fatty acids (SCFAs) in the large intestine, improving gut barrier function and immune response. Studies reveal GA’s promising roles in promoting beneficial gut bacteria and exhibiting antioxidant, anti-inflammatory, and immunomodulatory properties. However, comprehensive research is pivotal for optimizing its applications across diverse sectors and explaining its prebiotic mechanisms, emphasizing the necessity for standardized evaluation and increased awareness regarding its beneficial effects.